Development of AnkleReHabit - A Low-Cost Robot-Aided Ankle Rehabilitation Platform - Tran, Vi Do; Nguyen, Tu Gia Thinh; Nguyen, Tan-Nhu (Journal of Technical Education Science, 2023)
The ankle joint plays a critical part for human body weight support and daily movements. Any ankle joint injury can strongly affect the patient’s daily life, so ankle joint rehabilitation is essential to ensure the functional recovery of the ankle after ankle dysfunction. The AnkleReHabit system, a full system including both hardware and software for ankle rehabilitation training, was developed in this paper. To test the operation of the proposed system, one healthy subject has been enrolled. The AnkleReHabit system works well during the test with both Mobile App and serious game. The feedback from the enrolled subject shows that the system can be used with comfortable, the training process can be more exciting with the serious game developed on the computer. The AnkeReHabit platform was proven for feasibility in ankle rehabilitation training. Further work should include testing the effectiveness and the reliability of the AnkleReHabit system with the patients.